TAFSIR AL-QURAN DALAM NASKAH [MAJAZ]: Studi Filologis dan Analisis Isi - Mujahid, Ahmad (Fakultas Ushuluddin dan Humaniora IAIN Antasari, 2012)
In South Kalimantan, the manuscripts on tafsir up to this present were not found. TheÂ topics were dominated by the sufism and jurisprudence. This fact, actually become theÂ general phenomena in Indonesia. The manuscript was discussed here speak aboutÂ balaghah knowledge , especially on Majaz. By this manuscript, the writer want toÂ make a relation between manuscript of non-tafsir and the tafsirâs study. Here, theÂ writer use the filology approach, while for the tafsir, writer analyzed the verses in theÂ text using the tafsir approach. Actually, the verses were qouted here only five verses, evenÂ it part of the verses. The qouted verses here were examples of the quran than containedÂ the study of majaz. The explanation of writer on that verses of qurâan is a tafsirÂ according to the writes.